The dependence of star formation activity on environment and stellar mass at z similar to 1 from the HiZELS-H alpha survey - Sobral, D; Best, P; Best, P; Smail, I; Smail, I; Geach, J; Geach, J; Cirasuolo, M; Garn, T; Garn, T; Dalton, G (2012)
This paper presents an environment and stellar mass study of a large sample of star-forming Hα emitters at z= 0.84 from the High-z Emission Line Survey (HiZELS), over 1.3 deg 2 split over two fields (COSMOS and UKIDSS UDS). By taking advantage of a truly panoramic coverage of a wide range of environments, from the field to a rich cluster, it is shown that both stellar mass and environment play crucial roles in determining the properties of star-forming galaxies. Specific star formation rates (sSFRs) decline with stellar mass in all environments, and the fraction of Hα star-forming galaxies declines sharply from ≈40 per cent for galaxies with masses around 10 10M ⊙ to effectively zero above 10 11.5M ⊙, confirming that mass-downsizing is generally in place by z∼ 1. The fraction of star-forming galaxies is also found to fall sharply as a function of local environmental density from ≈40 per cent in the field to approaching zero at rich group/cluster densities. When star formation does occur in such high density regions, it is found to be mostly dominated by potential mergers and, indeed, if only non-merging star-forming galaxies are considered, then the environment and mass trends are even stronger and are qualitatively similar at all masses and environments, respectively, as in the local Universe. The median SFR of Hα emitters at z= 0.84 is found to increase with density for both field and intermediate (group or cluster outskirts) densities; this is clearly seen as a change in the faint-end slope of the Hα luminosity function from steep (α≈-1.9), in poor fields, to shallow (α≈-1.1) in groups and clusters. Interestingly, the relation between median SFR and environment is only found for low- to moderate-mass galaxies (with stellar masses below about 10 10.6M ⊙), and is not seen for the most massive star-forming galaxies. Overall, these observations provide a detailed view over a sufficiently large range of mass and environment to reconcile previous observational claims: stellar mass is the primary predictor of star formation activity at z∼ 1, but the environment, while initially enhancing the median SFR of (lower mass) star-forming galaxies, is ultimately responsible for suppressing star formation activity in all galaxies above surface densities of 10-30 Mpc -2 (group and cluster environments). © 2010 The Authors. Journal compilation © 2010 RAS.